Apathy and Disinhibition Related to Neuropathology in Amnestic Versus Behavioral Dementias. Issue 5 (August 2019) - Borges, Letizia G.; Rademaker, Alfred W.; Bigio, Eileen H.; Mesulam, M-Marsel; Weintraub, Sandra
Objectives: Investigating the frequency of apathy and disinhibition in patients clinically diagnosed with dementia of the Alzheimer type (DAT) or behavioral variant frontotemporal dementia (bvFTD) with neuropathology of either Alzheimer disease (AD) or frontotemporal lobar degeneration (FTLD). Methods: Retrospective data from 887 cases were analyzed, and the frequencies of apathy and disinhibition were compared at baseline and longitudinally in 4 groups: DAT/AD, DAT/FTLD, bvFTD/FTLD, and bvFTD/AD. Results: Apathy alone was more common in AD (33%) than FTLD (25%), and the combination of apathy and disinhibition was more common in FTLD (43%) than AD (14%; P < .0001). Over time, apathy became more frequent in AD with increasing dementia severity (33%-41%; P < .006). Conclusions: Alzheimer disease neuropathology had the closest association with the neuropsychiatric symptom of apathy, while FTLD was most associated with the combination of apathy and disinhibition. Over time, the frequency of those with apathy increased in both AD and FTLD neuropathology.